2020
DOI: 10.1186/s12886-020-01469-y
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging of aberrant macular microvessel crossing the foveal avascular zone in two young adults

Abstract: Background: The traditional view is that there are no vessels in the foveal avascular zone. The two cases we report show microvessels crossing the foveal avascular zone. Case presentation: A man and a woman, both 25 years old, were both incidentally found on optical coherence tomography angiography (OCTA) to have unilateral aberrant microvessels crossing the foveal avascular zone in their left eyes. Visual acuity was preserved in both patients. The vessel density (VD) and perfusion density (PD) of the eyes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…CRM in this patient had two another atypical feature. First, the macrovessel is usually seen to circumscribe around the foveola and rarely pass through its centre 4 10–12. However, the macrovessel passed through the centre of the FAZ in this patient.…”
Section: Discussionmentioning
confidence: 75%
“…CRM in this patient had two another atypical feature. First, the macrovessel is usually seen to circumscribe around the foveola and rarely pass through its centre 4 10–12. However, the macrovessel passed through the centre of the FAZ in this patient.…”
Section: Discussionmentioning
confidence: 75%
“…The presence of CRM caused the distortion of the FAZ, though the FAZ diameter was almost equal to the fellow eye. Previous reports of CRM have documented FAZ that were small or with interocular asymmetry [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…C ongenital retinal macrovessel (CRM) is defined as an abnormal large retinal vessel that encircles the foveal avascular zone (FAZ) [1] . Since the first description of a large aberrant vessel crossing the macula by Mauthner [2] in 1868, there have been several case reports about CRM [3][4][5][6][7][8][9][10] . And recently, Pichi et al [1] reported clinical manifestations and multimodal retinal imaging of 49 eyes with CRM.…”
Section: Dear Editormentioning
confidence: 99%